Stellar Contamination Correction Using Back-to-back Transits of TRAPPIST-1 b and c - Alexander D. Rathcke; Lars A. Buchhave; Julien de Wit; Benjamin V. Rackham; Prune C. August; Hannah Diamond-Lowe; João M. MendonÇa; Aaron Bello-Arufe; Mercedes López-Morales; Daniel Kitzmann; Kevin Heng (The Astrophysical Journal Letters)
Stellar surface heterogeneities, such as spots and faculae, often contaminate exoplanet transit spectra, hindering precise atmospheric characterization. We demonstrate a novel, epoch-based, model-independent method to mitigate stellar contamination, applicable to multiplanet systems with at least one airless planet. We apply this method using quasi-simultaneous transits of TRAPPIST-1 b and TRAPPIST-1 c observed on 2024 July 9, with JWST/NIRSpec PRISM. These two planets, with nearly identical radii and impact parameters, are likely to either be bare rocks or possess thin, low-pressure atmospheres, making them ideal candidates for this technique, as variations in their transit spectra would be primarily attributed to stellar activity. Our observations reveal their transit spectra exhibit consistent features, indicating similar levels of stellar contamination. We use TRAPPIST-1 b to correct the transit spectrum of TRAPPIST-1 c, achieving a 2.5 ×  reduction in stellar contamination at shorter wavelengths. At longer wavelengths, lower signal-to-noise ratio prevents clear detection of contamination or full assessment of mitigation. Still, out-of-transit analysis reveals variations across the spectrum, suggesting contamination extends into the longer wavelengths. Based on the success of the correction at shorter wavelengths, we argue that contamination is also reduced at longer wavelengths to a similar extent. This shifts the challenge of detecting atmospheric features to a predominantly white noise issue, which can be addressed by stacking observations. This method enables epoch-specific stellar contamination corrections, allowing coaddition of planetary spectra for reliable searches of secondary atmospheres with signals of 60–250 ppm. Additionally, we identify small-scale cold (∼2000 K) and warm (∼2600 K) regions almost uniformly distributed on TRAPPIST-1, with overall covering fractions varying by ∼0.1% per hour.